Enhanced dissolution of poorly soluble antiviral drugs from nanoparticles of cellulose acetate based solid dispersion matrices - Sonal Mazumder; Ashish Kumar Dewangan; Naresh Pavurala (Elsevier, 2017)
Polysaccharide-based polymers were used to produce nanoparticles of poorly soluble antiviral drugs using a rapid precipitation process. The structure-property relationships of four novel cellulose acetate-based polymers were studied for their solubility enhancement of poorly soluble drugs. Particles were purified by dialysis, and dried powders were recovered after freeze-drying. The particle diameters were 150-200 nm. The target drug loading in the particles was 25 wt%, and the drug loading efficiencies were 80-96%. The effects of the formulation process and nanoparticle properties on drug solubility were investigated. All nanoparticles afforded increased solubility and faster release compared to pure drugs. Drug release was a function of the relative hydrophobicity (or solubility parameters) of the polymers.